El feliz ingenio neomexicano : Felipe M. Chacón and Poesía y prosa - Chacón, F. M. (Felipe Maximiliano), 1873- (Book collections on Project MUSE., 2021)
"El feliz ingenio neomexicano is a bilingual recovery edition of Obras de Felipe Maximiliano Chacón, el Cantor Neomexicano: Poesía y prosa, the first collection of poetry published by a Mexican American author. Journalist and author Felipe M. Chacón, part of a distinguished and active family of nuevomexicano authors, published the book in 1924. El feliz ingenio neomexicano (that "inspired New Mexican wit") reestablishes Chacón's work and his reputation by making the text widely available to readers for the first time in nearly a century. With Nogar and Melendez's excellent translation of the text, this bilingual volume offers access to both English and Spanish editions for scholars and students from a variety of disciplines. Additionally, the in-depth introduction and appendix materials gathered by the editors place Chacón's book in the context of the time in which it was printed, offering a unique insight into the work. A welcome volume for scholars and literature lovers alike, El feliz ingenio neomexicano is a groundbreaking work of literary recuperation"--